Asymptotic analysis of the clamped-pinned elastica - Singh, P.; Goss, V.G.A. (Archives of Mechanics, 2018)
Asymptotic solutions for the clamped-pinned elastica when the displacement of the pinned end is small (immediately after buckling) and when it approaches its limiting displacement (when the force in the rod tends to infinity) are presented. Simple leading order relationships describing the force as a function of the pinned end’s displacement are derived. Those approximate the force-displacement behaviour of the clamped-pinned elastica for small and limiting end displacements. All our results are valid for the clamped-pinned elastica in any mode.